2018
DOI: 10.31224/osf.io/fv47e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MultiDIC: an Open-Source Toolbox for Multi-View 3D Digital Image Correlation

Abstract: Three-dimensional Digital Image Correlation (3D-DIC) is a non-contact optical-numerical technique for evaluating the dynamic mechanical behavior at the surface of structures and materials, including biological tissues. 3D-DIC can be used to extract shape and full-?eld displacements and strains with high resolution, at various length scales. While various commercial and academic 3D-DIC software exist, the field lacks 3D-DIC packages which offer straightforward calibration and data-merging solutions for multi-vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…A stereo camera rig was designed and fabricated, to hold up to 40 camera units. Each unit contains a Raspberry Pi Camera Module V2, featuring a Sony IMX219 8-megapixel 3.674 2.760 mm CMOS sensor, connected to a Raspberry Pi Zerow (see also [21]). All cameras were connected and synchronously controlled using an Ethernet hub connected to a PC.…”
Section: A Experimental Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…A stereo camera rig was designed and fabricated, to hold up to 40 camera units. Each unit contains a Raspberry Pi Camera Module V2, featuring a Sony IMX219 8-megapixel 3.674 2.760 mm CMOS sensor, connected to a Raspberry Pi Zerow (see also [21]). All cameras were connected and synchronously controlled using an Ethernet hub connected to a PC.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Prior to human subject testing, the camera configuration was verified by conducting preliminary tests on residual limb replicas (plaster cast molds), in order to ensure sufficient coverage and reconstruction accuracy. In the previous study, only 12 cameras, all having 30° between them, were used radially [21]. However, it was found that a narrower angle between the cameras is necessary for successfully reconstructing the anterior surface of the limb, especially around the anterior part of the knee, since these regions are typically characterized by higher curvatures than the rest of the limb.…”
Section: A Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, vision‐based sensing technology has been widely adopted in recent years for measuring the static and dynamic displacements of structural systems. For example, digital image correlation can provide high accuracy deformation measurement with high space resolution . Chen et al conducted a dynamic displacement‐field measurement based on RGB‐D sensor.…”
Section: Introductionmentioning
confidence: 99%